(untitled) (Bangladesh Heart Journal, 2022)
Background and objectives: Evaluation of ventricular systolic and diastolic functions is an essential part of echocardiographic evaluation in a patient of acute coronary syndrome (ACS). Myocardial Performance Index (MPI), also known as the Tei index, reflects both systolic and diastolic function of the left ventricle. The aim of this study was to see the association between myocardial performance index and severity of coronary artery diseases assessed by the gensini score (GS) in patients with non-ST segment elevation acute coronary syndrome. Methods: This cross-sectional study included a total 135 patients with NSTE ACS who underwent coronary angiography. MPI was measured using Pulse-Wave Doppler in all patients before coronary angiography. The patients were divided into three groups according to the Gensini score (GS); low GS < 19 (n=23); mid GS ³19 and £96 (n= 76); high GS > 96 (n=36) on CAG. Baseline characteristics, MPI parameters & GS were then compared between the three groups. Results: MPI was obtained successfully in 135 patients. MPI parameter was significantly increased with increased GS. MPI was positively correlated with the GS (r = 0.40, p < 0.001) Binary logistic regression analysis showed that MPI was strongly associated of severity of coronary artery disease assessed by GS (b = 3.766, p < 0.001). Conclusion: Patients with NSTE-ACS with severe coronary artery disease may be identified by means of MPI measurement. Key words: Tei Index, Gensini Score, Non-ST Segment Elevation Acute Coronary Syndrome, Coronary Angiogram. Bangladesh Heart Journal 2022; 37(1): 16-26